The gelling properties of Dillenia indica mucilage in benzyl benzoate emulgel formulations (2020)
The objective of the study was to evaluate the gelling properties of Dillenia indica mucilage in benzyl benzoate emulgel formulation. Mucilage was extracted from the fruits of Dillenia indica using established methods and characterized by rheology and swelling. Emulsion (F1) was prepared using the continental emulsification method. Gelling agents (2 %w /v) were prepared by dispersing in distilled water with constant stirring at a moderate speed usinga magnetic stirrer. F1 was added to the gel (0-75 %w /w) to obtain emulgel formulations and evaluated using viscosity, globule size, pH, release profiles and kinetic modeling. Data were expressed as mean ± SD, and similarity factor (f2) was used to compare all formulations. Formulation viscosity was significantly higher with carbopol than with Dillenia; globule sizes increased with concentration of gelling agents, and pH reduced as the concentration of Dillenia increased. All formulations showed controlled release properties with t80 ranging between 114 and 660 min. The release was governed by Korsmeyer-Peppas model. Formulation F5 prepared with 50 % Dillenia showed highest similarity to F4 prepared with 75 %w /w carbopol. Dillenia indica demonstrated acceptable gelling properties comparable with that of carbopol and could be improved for use in emulgel formulations.